The Influence of Service Quality, Price, and Customer Satisfaction on Customer Loyalty of Tenun Ikat ‘Medali Mas’ in Kediri City - Denvi Nur Mei Wardani; Enni Sustiyatik; IGG Heru Marwanto (Journal of Innovative and Creativity, 2025)
This research aims to determine the effect of service quality and price on loyalty through customer satisfaction of Bandar Kediri ikat weaving customers. This type of research uses descriptive quantitative with a survey approach where questionnaires will be distributed to all research respondents who are the population in this study, namely consumers who have purchased gold medal ikat woven cloth more than once, taken in January - March 2023, which is not yet known for certain. The number was used so that the formula for determining the sample size according to Wibisono was used, where 100 respondents were obtained as samples. Path analysis was used to test the results of respondent data to measure the influence of the dependent variable on the independent variable. Based on the test results, it was found that service quality has a significant effect on customer satisfaction, price has a significant effect on customer satisfaction, service quality has a significant effect on customer loyalty, price has no significant effect on customer loyalty, and customer satisfaction mediates the effect of service quality on customer loyalty.